Assessing Stability: Geotechnical Analysis of Landfill Sites - Goren, Sami (European Journal of Applied Sciences, 2024)
Most people live in a society surrounded by limited space in cities. One of the basic activities of a human is feeding himself, which allows him to continue the struggle of life. Eating, drinking and cleaning activities are inevitable in human life. All of these activities generate solid, liquid or gas waste and these wastes should be removed from daily life as quickly as possible in order to remove the nuisances to the public. The rapid growth of urbanization and industrialization has made it necessary to find new ways of waste disposal. Waste Management (WM) is the solution for the public and for the environment to maintain health, hygiene and aesthetical view. Landfilling is one of the most common methods used worldwide for solid waste management. Landfill sites play a significant role in waste management; nevertheless, as the amount of waste increases, more material is brought to landfills. Dangerous mishaps may occur if improper management practices are not implemented at the landfills. Due to the nature of waste, landfills face a number of stability issues that pose a threat to resilience and safety. This study intends to provide an overview of the topic of landfill site stability and examine the solution to landfill accidents caused by improper operation and maintenance.